Epidemiology and molecular phylogeny of Babesia sp. in Little Penguins Eudyptula minor in Australia. Issue 2 (August 2015) - Vanstreels, Ralph Eric Thijl; Woehler, Eric J.; Ruoppolo, Valeria; Vertigan, Peter; Carlile, Nicholas; Priddel, David; Finger, Annett; Dann, Peter; Herrin, Kimberly Vinette; Thompson, Paul; Ferreira Junior, Francisco C.; Braga, Érika M.; et al.
Highlights: We examined blood smears from 263 wild little penguins in southeastern Australia. Babesia sp. was detected in penguins in New South Wales, Victoria and Tasmania. True prevalence is estimated between 3.4% and 4.5%. Babesia sp. from little penguins is closely related to B. poelea and B. uriae . Babesia infections were assymptomatic. Graphical Abstract: Abstract: Blood parasites are potential threats to the health of penguins and to their conservation and management. Little penguins Eudyptula minor are native to Australia and New Zealand, and are susceptible to piroplasmids ( Babesia ), hemosporidians ( Haemoproteus, Leucocytozoon, Plasmodium ) and kinetoplastids ( Trypanosoma ). We studied a total of 263 wild little penguins at 20 sites along the Australian southeastern coast, in addition to 16 captive-bred little penguins. Babesia sp. was identified in seven wild little penguins, with positive individuals recorded in New South Wales, Victoria and Tasmania. True prevalence was estimated between 3.4% and 4.5%. Only round forms of the parasite were observed, and gene sequencing confirmed the identity of the parasite and demonstrated it is closely related to Babesia poelea from boobies ( Sula spp.) and B. uriae from murres ( Uria aalge ). None of the Babesia -positive penguins presented signs of disease, confirming earlier suggestions that chronic infections by these parasites are not substantially problematic to otherwise healthy little penguins. We searched also for kinetoplastids, and despite targeted sampling of little penguins near the location where Trypanosoma eudyptulae was originally reported, this parasite was not detected.